Lexical Complexity and Readibility Realized in The Introduction Sections of Selected English Journals - Mayangsari, Andhani; Wuli Fitriati, Sri; Sutopo, Djoko (English Education Journal, 2021)
This study focused on the analysis of lexical complexity of the introduction section of the English journals manifested in lexical density, lexical diversity and lexical sophistication. This study also investigated the readability level of those texts. The method used in this study was a quantitative study by utilizing lexical complexity and readability analysis. The results of the study show that the manifestation of lexical density of the texts was above 0.50, representing that the content words utilized within the text were higher than function words. Furthermore, most of the introduction sections of the selected English journals achieved lexical diversity level more than 0.30 in which the highest lexical diversity was shown by EEJ journals and EduLite journals that shared the same level of lexical diversity with 0.35. Besides, the introduction sections were composed of. various advanced lexical items in terms of Academic Word Lists (AWL). Also, all introduction sections of the English journals - EEJ, EduLite and IJAL was readable for English department students both undergraduate and graduate degree based on Flesch Kincaid Reading Ease, Flesch Kincaid Grade Level and Miyazaki readability index. It is suggested that the journals’ introduction sections should be composed of informationally dense lexical items covering the important ideas to strengthen the arguments. It is expected that further studies could investigate more about other aspects that determine the quality of English journals’ introduction sections to uncover deeply about the quality of the texts.